2021
DOI: 10.1108/jmhtep-07-2021-0087
|View full text |Cite
|
Sign up to set email alerts
|

Using traditional medicine to help with bereavement loss and coping: an interpretative phenomenological analysis of traditional healers’ experiences

Abstract: Purpose In bereavement, memories of the loss, especially traumatic ones, can be distressful and complicate the grieving process. Although some conventional therapies have proven beneficial in lessening complicated bereavement, African indigenous methods used for the same purpose have not been well-documented. This study explored Northern Sotho traditional healers’ lived experiences regarding the medicinal benefits of Bolebatša when used in mental health-care. Design/methodology/approach Using interpretative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
4
2
Order By: Relevance
“…Similarly, it has been reported that cultural and religious beliefs play a significant role in mental health treatment in Nigeria (Jidong et al 2022 ). One participant in the present study reported the inadequacy of using traditional herbs in treating BDs contrary to a previous study that reported traditional medicines to help with bereavement loss, trauma and coping with mental health disorders in South Africa (Makgahlela et al 2021 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Similarly, it has been reported that cultural and religious beliefs play a significant role in mental health treatment in Nigeria (Jidong et al 2022 ). One participant in the present study reported the inadequacy of using traditional herbs in treating BDs contrary to a previous study that reported traditional medicines to help with bereavement loss, trauma and coping with mental health disorders in South Africa (Makgahlela et al 2021 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Similarly, it has been reported that cultural and religious beliefs play a signi cant role in mental health treatment in Nigeria (Jidong et al, 2022). One participant in the present study reported the inadequacy of using traditional herbs in treating BDs was contrary to a previous study that reported traditional medicines to help with bereavement loss, trauma and coping with mental health disorders in South Africa (Makgahlela et al, 2021).…”
Section: Discussioncontrasting
confidence: 74%
“…Cultural belief systems and traditional practices play essential roles in how people think, act or engage in mental health-seeking behaviours (Helman, 2007;Makgahlela et al, 2021). Mental health is subjective and could be defined in linguistic expression, community orientation, social expectation or cultural identity (Jidong et al, 2020;O'Neill, 2005;Vaillant, 2012).…”
Section: Introductionmentioning
confidence: 99%